Financial Ratios and Stock Prices in Automotive Companies: Faktor-faktor yang Mempengaruhi Perilaku Konsumtif Mahasiswa dalam Konteks E-Commerce - Mukharomah , Anis Krismawati; Hanif, Aisha (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Stock prices are a key indicator for investors in assessing firm value in capital markets. Specific Background: Financial ratios are widely used to evaluate company performance in the automotive and component subsector listed on the Indonesia Stock Exchange. Knowledge Gap: Limited studies examine profitability, liquidity, and leverage ratios simultaneously with earnings per share as a moderating variable in this subsector. Aims: This study examines the relationship between Return on Assets, Current Ratio, and Debt to Equity Ratio on stock prices with Earnings per Share as a moderating variable. Results: The findings show that Return on Assets, Current Ratio, and Debt to Equity Ratio are statistically associated with stock prices, while Earnings per Share moderates these relationships. Novelty: The study integrates earnings per share as a moderating variable within a financial ratio framework in automotive companies. Implications: The results provide insights for investors and researchers in evaluating stock price movements using financial statement information. Keywords: Stock Price, Return On Assets, Current Ratio, Debt To Equity Ratio, Earnings Per Share Key Findings Highlights: Profitability indicators show a consistent relationship with market valuation. Liquidity and leverage ratios are linked to variations in share values. Earnings per share strengthens the association between financial ratios and stock valuation.